Archean komatiite volcanism controlled by the evolution of early continents - Mole, D.; Fiorentini, M.; Thebaud, N.; Cassidy, K.; McCuaig, C.; Kirkland, Chris; Romano, S.; Doublier, M.; Belousova, E.; Barnes, S.; Miller, J. (PNAS, 2014)
The generation and evolution of Earth’s continental crust has played a fundamental role in the development of the planet. Its formation modified the composition of the mantle, contributed to the establishment of the atmosphere, and led to the creation of ecological niches important for early life. Here we show that in the Archean, the formation and stabilization of continents also controlled the location, geochemistry, and volcanology of the hottest preserved lavas on Earth: komatiites. These magmas typically represent 50–30% partial melting of the mantle and subsequently record important information on the thermal and chemical evolution of the Archean–Proterozoic Earth. As a result, it is vital to constrain and understand the processes that govern their localization and emplacement. Here, we combined Lu-Hf isotopes and U-Pb geochronology to map the four-dimensional evolution of the Yilgarn Craton, Western Australia, and reveal the progressive development of an Archean microcontinent. Our results show that in the early Earth, relatively small crustalblocks, analogous to modern microplates, progressively amalgamated to form larger continental masses, and eventually the first cratons. This cratonization process drove the hottest and most voluminous komatiite eruptions to the edge of established continental blocks. The dynamic evolution of the early continents thus directly influenced the addition of deep mantle material to the Archean crust, oceans, and atmosphere, while also providing a fundamental control on the distribution of major magmatic ore deposits.